Entwicklung und Optimierung des Diffusionsschweißens von ODS Legierungen - Sittel, Wiebke (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2014)
The requirements for structural materials for generation IV atomic power plants are becoming more demanding since increased efforts are being made in order to build more efficient and sustainable reactors. Oxide dispersion strengthened (ODS) steels show a fine high temperature and irradiation stability. This study presents a model for the prediction of the optimal bonding parameters of the solid state bonding technique diffusion bonding. It is optimized by means of an experimental evaluation.